Average Joe [videorecording (DVD)] - Katz, Stephanie, 1991-; Close, Eric; Rae, Paul; Woods, Austin (Universal Studios, 2024)
High school football coach Joe Kennedy had no other choice but to fight. A childhood in foster care followed by 20 years in the Marine Corps was nothing compared to his biggest battle: his commitment to stand for God publicly by taking a knee in prayer after each game. When he was fired, Joe and his wife Denise knew this battle for religious freedom, freedom of speech, and the rights of all Americans was one they would have to fight no matter the cost.